Faktor – factor yang Mempengaruhi Komitmen Organisasi Karyawan Restoran Cepat Saji di Batam - Yuswardi Yuswardi; Budi Harsono (Politeknik Ganesha Medan, 2019)
This study is aimed to determine the effect of working environment, compensation, job engagement, and job security on employees’ organizational commitment of employees of four fast food chains restaurant in Batam. This study was conducted by distributing questionnaires to 400 employees of five biggest national bank branches in Batam. There’re 380 questionnaires collected back and filled out completely and then analized by using SPSS. Data processing shown that there are relationships between all the variables studied. Results of this showed that there’re relations between working environment, compensation, job engagement, job security to employee commitment. This studiy emphasizes the importance for fast food chains restaurant management to pay more attention to the variables studied above. Because all of the above variables closely linked to the commitment of the employees, so that if the company wanted to improve the commitment of employees then all variables above should be enhanced and improve